Photosynthetic Characteristics of Resistance and Susceptible Lines to High Temperature Injury in Panax ginseng Meyer - Lee, Joon Soo (The Korean Society of Ginseng, 2012)
In this study, photosynthetic parameters such as the net photosynthesis rate, stomatal conductance, intercellular CO(2) concentration, and transpiration rate were examined in selected ginseng varieties and/or lines that are resistant (Yunpoong, HTIR 1, HTIR 2, and HTIR 3) and susceptible (Chunpoong) to high temperature injury (HTI). The net photosynthesis rate increased with the increase in the light intensity in all the HTI-resistant and -susceptible ginseng lines with a light saturation point of 200 μmol m(-2)s(-1), except for Yunpoong that had a light saturation point of 400 μmol m(-2)s(-1). At the light saturation point, the net photosynthesis rate in July was highest in HTIR 3, at 4.2 μmol CO(2) m(-2)s(-1), and was lowest in Yunpoong, HTIR 1, Chunpoong, and HTIR 2, in that order, at 1.9 to 3.7 μmol CO(2) m(-2)s(-1). The net photosynthesis rate in August was highest in Yunpoong at 5.9 μmol CO(2) m(-2)s(-1), and lowest in HTIR 1 and HTIR 3 (4.5 μmol CO(2) m(-2)s(-1)) and in other lines, in that order, at 2.8 to 2.9 μmol CO(2) m(-2)s(-1). The stomatal conductance in July was highest in HTIR 3 (0.055 mol H(2)O m(-2)s(-1)) and Yunpoong, Chunpoong, HTIR 1, and HTIR 2 were 0.038, 0.037, 0.031, and 0.017 in that orders. In August, meanwhile, HTIR 1 showed the highest as 0.075, and followed by HTIR 3, Chungpoong, and HTIR 2 with 0.070, 0.047, and 0.023, respectively. The intercellular CO(2) concentration at the light saturation point in July and August was much lower in HTIR 2 at 139 and 185 μmol mol(-1) than in the other ginseng lines at 217 to 257 and 274 to 287 μmol mol(-1), respectively. The transpiration rate in July and August was higher in the HTI-resistant lines of Yunpoong, HTIR 1, and/or HTIR 3 at 0.83 to 1.03 and 1.67 to 2.10 mol H(2)O m(-2)s(-1) than in the other ginseng lines at 0.27 to 0.79 mol H(2)O m(-2)s(- 1) and 0.51-1.65 mol H(2)O m(-2)s(-1), respectively. Conclusively, all the photosynthetic parameters that were examined in this study were generally higher in the HTI-resistant ginseng lines than in the HTI-susceptible lines, except for HTIR 2, and were much higher in August than in July, especially in the resistant ginseng lines. All these results can be used to provide basic information for the selection of HTI-resistant ginseng lines and the application of cultural practices that are efficient for ginseng growth, based on the photosynthetic characteristics of the lines.